2000
DOI: 10.1023/a:1002856003897
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ultrastructural changes in the population of pathogenic Yersinia pseudotuberculosis inhabiting a model soil ecosystem for a long time were studied. Changes in the bacteria were mainly adaptive until the 8th month of the experiment, their capacity to binary division was preserved. After 9 months cell structure changed: extracellular amorphous matrix appeared, probably due to increased mucus production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A generalization of the results of studies obtained during model experiments made it possible to establish a complex of ultrastructural changes in the FESLF causative agent under different ecological conditions similar to those in a warm-blooded organism and the environment. It was concluded that these changes in bacteria of periodic and soil cultures that ensure their functional usefulness should be considered as an adaptive response of bacterial populations to changing living conditions, which demonstrates the universal, morphological mechanism of their adaptation [30,31]. A long stay of Y. pseudotuberculosis in the soil is provided by phenotypic changes at the ultrastructure level and is expressed in the formation of a capsule and microcapsule, general cover, mucus, intercellular contacts, cytoplasmic outgrowths (prostakes), and accumulation of reserve substances [25,27,32].…”
Section: Morphological Aspects Of the Y Pseudotuberculosis Adaptation To Various Living Conditionsmentioning
confidence: 99%
“…A generalization of the results of studies obtained during model experiments made it possible to establish a complex of ultrastructural changes in the FESLF causative agent under different ecological conditions similar to those in a warm-blooded organism and the environment. It was concluded that these changes in bacteria of periodic and soil cultures that ensure their functional usefulness should be considered as an adaptive response of bacterial populations to changing living conditions, which demonstrates the universal, morphological mechanism of their adaptation [30,31]. A long stay of Y. pseudotuberculosis in the soil is provided by phenotypic changes at the ultrastructure level and is expressed in the formation of a capsule and microcapsule, general cover, mucus, intercellular contacts, cytoplasmic outgrowths (prostakes), and accumulation of reserve substances [25,27,32].…”
Section: Morphological Aspects Of the Y Pseudotuberculosis Adaptation To Various Living Conditionsmentioning
confidence: 99%